MEMBANGKITKAN UMKM MELALUI USAHA KERIPIK UBI PEDAS DI DESA PERMATA BARU - Lisdiana, Lisdiana; Dewi, Inne Miftah; Wahidin, Wahidin; Ferahwati, Ferahwati; Anggraini, Dian; Aplianto, Andika (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2023)
The Covid-19 pandemic has had a significant impact on all aspects, one of which is for culinary business actors. The aim of community service activities is to encourage the rise of MSMEs through the spicy sweet potato chips business in the era of the Covid-19 pandemic to reduce the number of social problems in Permata Baru Village, North Indralaya District, Ogan Ilir Regency. The activities were carried out for one month with several activity agendas that had been prepared in a planned manner by the STISIPOL Candradimuka community service team. This activity uses socialization and training as implementing methods. The results of the activity are training in making product labels to support the branding of spicy sweet potato chips so that they are widely known by consumers; introduction and strengthening of relationships between BUMDes and business actors to support product marketing; as well as outreach related to production and inventory management and financial management. Thus, this activity has a positive impact on the business community, namely increasing the ability to innovate and being able to adapt to market changes.